Effect of probiotic capsules on preventing gestational diabetes among high-risk prediabetic pregnant women - Mahdieh Ebrahimzadeh; Samira Ebrahimzadeh Zagami; Masoumeh Kordi; Mohmmad Taghi Shakeri; Seyed Ahmad Emami; Farideh Akhlaghi (Mashhad University of Medical Sciences, 2020)
Introduction: Gestational diabetes is the most common medical condition in pregnancy. Since probiotics are viable microorganisms which have beneficial effects on microbial flora of the intestine, they affect glucose metabolism. Therefore, this study was performed with aim to determine the effect of probiotic capsule on the prevention of gestational diabetes in high risk pre-diabetes pregnant women. Methods: This double-blind clinical trial study was performed on 255 high risk pre-diabetic pregnant women in health centers covered by health center No.2 of Mashhad in 2018. In the probiotic group and the placebo group, in addition to routine care, one probiotic capsule and placebo were daily prescribed respectively from 14-16 weeks of gestation for 12 weeks. Then, glucose tolerance test (OGTT) was performed at week 26-28. The research tools included demographic and midwifery information form, checklist of pregnancy diabetes screening tests, drug use checklist, examination form and satisfaction form. Data were analyzed using SPSS software (version 22), and Chi-square, One-way ANOVA, Kruskal - Wallis and Mann-Whitney tests. P<0.05 was considered statistically significant. Results: 21 patients (26.3%) in the probiotic group, 49 (59.8%) in the placebo group, and 55 (67.1%) in the control group had gestational diabetes (P<0.001). Gestational diabetes in the intervention group was significantly less than the placebo and control group. The results of the Chi-square Pearson test for two by two comparison of the groups showed significant difference in gestational diabetes mellitus between probiotic group with placebo (P <0.001) and probiotic group with control (P <0.001). Gestational diabetes in the intervention group in significance level of lower than 5% was lower than the placebo and control group. Conclusion: The use of probiotic capsules can be recommended to high risk pregnant women in preventing gestational diabetes.